(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
Feed formulations through linear models are an alternative to satisfy the adequate nutritional requirements of birds at a minimum cost, which is why the objective of the research is the development of the feed, its proximal evaluation and digestibility for birds in the initial stage. which included moringa Oleifera lam and yucca Manihot esculenta. The methodological design consisted of: proximal characterization of moringa flour and cassava flour, food formulation, II proximal analysis of the formulated food and its in vitro digestibility of the balanced food and finally Establishment, organization of control/experimental group under application of the treatment. The data obtained in the first two phases were analyzed with descriptive statistics in the STATGRAPHICS package and Linear programming by TORA. The most relevant results were: moringa flour has a protein content of 20.40% of which 70.22% is digestible. The solution to the objective function of the formulation was to minimize the cost of the product, resulting in a total price of 52,147.39 Bs based on the production of 40 kg. The formulated food presented values ​​of 24.67% protein, metabolizable energy of 2893 kcal/kg and a digestibility of 73.67%, complying with the requirements of the COVENIN 1881-83 standard. Spanish.